2014
DOI: 10.7314/apjcp.2014.15.16.6499
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Health Information-Seeking Behavior: Implications for Post-Treatment Cancer Patients

Abstract: Health knowledge is necessary for personal healthcare management. The public obtains such health knowledge not only from healthcare providers, but also through daily media exposure. Health information became highly universalized amid a wave of health news, pharmaceutical advertisements, and health websites coupled with the recent emergence of user-generated Internet content (i.e. blogs) based on diverse information and communication platforms. Despite the abundance of health information, however, huge disparit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 73 publications
4
46
0
Order By: Relevance
“…An individual’s perceived need for medical care is one of the major promoting factors of healthcare-seeking behavior [36]. In the multivariable model, those who reported feeling less fertile than age –matched women had significantly higher odds of using FC after their cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…An individual’s perceived need for medical care is one of the major promoting factors of healthcare-seeking behavior [36]. In the multivariable model, those who reported feeling less fertile than age –matched women had significantly higher odds of using FC after their cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Seeking and finding health information in order to cope with a health threatening situation is one of the most frequent goals of engaging in HISB. Of the literature reviewed, much of itthat is germane to this contextis produced in relation to diabetes, cancer and chronic illness (Blanch-Hartigan, Blake, & Viswanath, 2014; Dean et al, 2017;Graffigna, Barello, Bonanomi, & Riva, 2017;Jamal et al, 2015;Jung, 2014;Jung, 2015;Kratzke, Wilson, & Vilchis, 2013;Lambert et al, 2009a;Lee, Hoti, Hughes, & Emmerton, 2014;Longo et al, 2009;Longo et al, 2010;Mayer et al, 2007;Ramasamy, Singh, Mohan, & Meenakshi, 2016;Zare-Farashbandi, Lalazaryan, Rahimi, & Hassanzadeh, 2016).…”
Section: Hisb In the Context Of Coping With A Health Threatening Situmentioning
confidence: 99%
“…outcomes included collecting information about diseases, health conditions, treatments or procedures (Campbell, 2009;Shahrokni et al, 2015); increased health knowledge (Bahkali et al, 2016); and an enhanced ability to engage in shared decision making regarding medical treatment (Jung, 2014). The behavioural outcomes considered were highly variant.…”
Section: Cognitivementioning
confidence: 99%
“…[28] The study by Jung in this regard indicated that the more the thoughts about the illness likelihood among individuals, the more they feel the need to cope with and reduce unnecessary health concerns, perform preventive behaviors, and promote self-efficacy, and they carry out more purposeful seeking. [38] Therefore, they are less likely to pay attention to the barriers to obtaining health information and try to obtain the information they need regardless of the barriers and are more willing to get the information they require.…”
Section: Discussionmentioning
confidence: 99%